Menelusuri Amalan Keagamaan dalam Kalangan Gelandangan Muslim (Jurnal Pembangunan Sosial, 2017)
Homeless life is one of the social issues for the country including Malaysia. It can expose these group to many kinds of problem such as health, safety, welfare and so on. These article try to highlight the religiosity practice among homeless people. This aspect had been stressed out as research questions due to their difficulties of practicing worship. Hence, the qualitative research has been conducted in Penang, Malaysia involve 11 respondents among Muslims homeless. The face to face semi structure interviews method had been done by researchers using questionnaire contained the islamic religious practice. Besides, the focused group discussion (FGD) session had been done with six subject who involve directly with homeless issues. The raw data was manually analyzed using content analysis method and in order to search specific themes for answering research questions. The findings showed that the level aspect of religiosity practice among homeless people was in low level. This finding was almost matched with the result from the FGD that stated the home and hygine factors that lead to ignorance of religious practice. Therefore, this research suggest that religious aspect should be emphasized in order to help homeless people other than material assistance such as finance and food. The one stop centre such as ‘anjung singgah’ can help these homeless to proceed their duty as Muslims and their hygines. Other than that, there should be the religious people to give some Islamic interventions to them as well.